Thrombolysis with Streptokinase in Rabbits Dose Response, Fibrin-clot Specificity and Laboratory Evaluation of Fibrinolytic Effect - Nowak, Andrzej; Gurewich, Victor (Thrombosis and Haemostasis, 1974)
An animal model was used in which venous thromboemboli of reproducible size could be formed. The effects of SK 500–50,000 units per hour were evaluated and compared to those of saline. Proportionately the greatest clot lysis occurred with the lowest doses of SK. In contrast to thrombolysis, significant fibrinogenolysis did not occur in any of the animals indicating a high degree of specificity of SK-induced activator for rabbit fibrin. An excellent correlation between the concentration of fibrin degradation products (fdp) measured by the serial dilution protamine sulfate test and the extent of clot lysis was found suggesting this to be a useful method for monitoring the effects of thrombolytic therapy. A method for the laboratory distinction of fdp from fibrin monomer was demonstrated.